The Art of Goodbye: Communication Considerations - Suzanna D. Smith; Lynda Spence; Chelsea Tafelski (EDIS)
People are frequently at a loss for the best way to begin a discussion about end-of-life concerns with loved ones and health care providers, and are also unsure of the topics they should cover. Nonetheless, conversations about end-of-life care and advance directives can help ensure that the person’s wishes are honored. These measures also eliminate much of the difficult decision-making that loved ones typically face at the time of their loved ones’ passing. This 5-page fact sheet, which is part of a series entitled The Art of Goodbye: End of Life Education series, discusses the barriers to discussing the end of life and the process of communication with loved ones and health care providers. Written by Suzanna Smith, Lynda Spence, and Chelsea Tafelski, and published by the UF Department of Family, Youth and Community Sciences, October 2016.